2020
DOI: 10.1007/s11079-020-09597-0
|View full text |Cite
|
Sign up to set email alerts
|

Government Revenue and Child and Maternal Mortality

Abstract: Most maternal and child deaths result from inadequate access to the critical determinants of health: clean water, sanitation, education and healthcare, which are also among the Sustainable Development Goals. Reasons for poor access include insufficient government revenue for essential public services. In this paper, we predict the reductions in mortality rates — both child and maternal — that could result from increases in government revenue, using panel data from 191 countries and a two-way fixed-effect linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Like Filmer and Pritchett, Jamison, Murphy, and Sandbu (2016) and many of the empirical studies analysed by O' Hare et al (2013) use a log formulation in a panel data study to derive comparable elasticities (O'Hare et al 2013;Jamison, Murphy, and Sandbu 2016). Hall et al (2020) also conducted a large panel data study, but they found that the double log specification was outperformed by a model with exponential decay of the effect of government revenue per capita on under-five and maternal mortality (they calculated government revenue per capita by multiplying the government revenue as a percentage of GDP by GDP per capita in constant 2010 USD) (Hall et al 2020). This paper's purpose is twofold: first, we consider an alternative non-linear specification based on survival rates rather than mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…Like Filmer and Pritchett, Jamison, Murphy, and Sandbu (2016) and many of the empirical studies analysed by O' Hare et al (2013) use a log formulation in a panel data study to derive comparable elasticities (O'Hare et al 2013;Jamison, Murphy, and Sandbu 2016). Hall et al (2020) also conducted a large panel data study, but they found that the double log specification was outperformed by a model with exponential decay of the effect of government revenue per capita on under-five and maternal mortality (they calculated government revenue per capita by multiplying the government revenue as a percentage of GDP by GDP per capita in constant 2010 USD) (Hall et al 2020). This paper's purpose is twofold: first, we consider an alternative non-linear specification based on survival rates rather than mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that most governments seek to achieve a threshold level of defence spending irrespective of development and tax levels, and that defence spending accounts for a disproportionately high share of outlays in many of the lowest-taxed and poorest countries. While correlation does not imply causation, these trends suggest that increased tax revenue will often be directed towards development-promoting areas, a claim strengthened by more detailed empirical evidence on taxes and health spending (Carter andCobham 2016 andHall et al 2021).…”
Section: Developing Asia's Public Expenditure Landscapementioning
confidence: 96%
“…While correlation does not imply causation, these trends suggest that increased tax revenue will often be directed towards development‐promoting areas, a claim strengthened by more detailed empirical evidence on taxes and health spending (Carter and Cobham 2016 and Hall et al 2021).…”
Section: Developing Asia's Tax and Expenditure Landscapementioning
confidence: 98%
“…An increase in revenue has much more impact when the government revenue per capita is small, highlighting that an increase in revenue would have a much more significant effect on low-and lower-middle-income countries. Government revenue also reflects the spending capacity for all sectors, which indirectly affects health, including education and infrastructure [11].…”
Section: Government Revenue and The Determinants Of Healthmentioning
confidence: 99%
“…The best model of this non-linearity is a version of an inverse function that starts with minimal effects for countries with low government revenue per capita; the impact rapidly increases until a saturation point or plateau is reached, and the impact of an increase in revenue on the SDGs slows. Thus countries with small per-capita government revenues have a better scope for progress towards the SDGs with small revenue increases [11]. Rather than impose the same sigmoid shape across all countries, the modelling includes six dimensions of governance from the World Governance Indicators [41], allowing an individual 'sigmoid' 'S' shape, which varies for each country as governance and revenue change.…”
Section: The Grade-estimating the Impact Of An Increase In Government...mentioning
confidence: 99%